New Materials for Thin-Film Solid-Phase Microextraction (TF-SPME) and Their Use for Isolation and Preconcentration of Selected Compounds from Aqueous, Biological and Food Matrices - Witold Krumplewski; Iwona Rykowska (Molecules, 2024)
Determination of a broad spectrum of analytes, carried out with analytical instruments in samples with complex matrices, including environmental, biological, and food samples, involves the development of new and selective sorption phases used in microextraction techniques that allow their isolation from the matrix. SPME solid-phase microextraction is compatible with green analytical chemistry among the sample preparation techniques, as it reduces the use of toxic organic solvents to the minimum necessary. Over the past two decades, it has undergone impressive progress, resulting in the development of the thin-film solid-phase microextraction technique, TF-SPME (the thin-film solid-phase microextraction), which is characterized by a much larger surface area of the sorption phase compared to that of the SPME fiber. TF-SPME devices, in the form of a mostly rectangular metal or polymer substrate onto which a thin film of sorption phase is applied, are characterized, among others, by a higher sorption capacity. In comparison with microextraction carried out on SPME fiber, they enable faster microextraction of analytes. The active phase on which analyte sorption occurs can be applied to the substrate through techniques such as dip coating, spin coating, electrospinning, rod coating, and spray coating. The dynamic development of materials chemistry makes it possible to use increasingly advanced materials as selective sorption phases in the TF-SPME technique: polymers, conducting polymers, molecularly imprinted polymers, organometallic frameworks, carbon nanomaterials, aptamers, polymeric ionic liquids, and deep eutectic solvents. Therefore, TF-SPME has been successfully used to prepare analytical samples to determine a broad spectrum of analytes in sample matrices: environmental, biological, and food. The work will be a review of the above-mentioned issues.